Synthesis and evaluation of oxime derivatives as modulators for amyloid beta-induced mitochondrial dysfunction - Kim, Young Seub; Jung, Sun Hwa; Park, Beoung-Geon; Ko, Min Kyung; Jang, Hyun-Seo; Choi, Kihang; Baik, Ja-Hyun; Lee, Jiyoun; Lee, Jae Kyun; Pae, Ae Nim; Cho, Yong Seo; Min, Sun-Joon (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2013)
Starting from quinuclidinyl oxime 1 identified by preliminary screening, a series of azacycles-containing oxime derivatives was synthesized. Their mPTP blocking activities were evaluated by a JC-1 assay, measuring the change of mitochondrial membrane potential. The inhibitory activity of nine compounds against amyloid beta-induced mPTP opening was comparable or even superior to that of piracetam. Among them, 12d effectively maintained mitochondrial function and cell viabilities on the ATP assay, the MTT assay, and the ROS assay. In addition, it exhibited favorable in vitro stability and pharmacokinetic characteristics, which hold a promise for further development of AD therapeutics. (C) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: PERMEABILITY TRANSITION; ALZHEIMERS-DISEASE; DIMEBON; TRANSPORT; ENHANCER